Pengembangan Lembar Kerja Peserta Didik (LKPD) pada Pembelajaran Tematik di Kelas V SD Islam Terpadu NU Tanjung Baru T. A. 2022-2023 - Rahmasari, Rizki; Harahap, Syarifah Ainun; Herdyana, Thessa (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
This study aims to address the lack of development of thematic LKPD (Student Worksheets) at NU Tanjung Baru Integrated Islamic Elementary School. Utilizing the Research and Development (R&D) methodology, this research followed ten structured stages: identifying potential problems, data collection, product design, product validation, design revision, product trial, product revision, usage trial, further revision, and mass production. Expert assessments from material, media, and language reviewers yielded scores in the "very appropriate" category, indicating high feasibility. The developed LKPD was subsequently tested with students to evaluate its effectiveness. Trial results showed a "very good" response category, reflecting strong engagement and improved learning outcomes. These findings demonstrate the practicality and relevance of the thematic LKPD in enhancing educational quality and student learning experiences. The study underscores the need for continuous innovation in instructional materials to support student-centered learning and foster improved academic performance in integrated Islamic schools.